Intensity of exercise according to topography in professional cyclists - Rodriguez-Marroyo, J. A.; Garcia Lopez, J.; Avila, C.; Jimenez, F.; Cordova, A.; Villa Vicente, J. G. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: The aim of the study was to analyze the intensity of effort made by professional cyclists in the different mountain passes climbed during the 1999 and 2000 Vuelta a Espana. METHODS: During the ascent of high mountain passes of different categories (special category (HMS), and 1st (HM1), 2nd (HM2), and 3rd category (HM3)), the response of the HR was analyzed according to three intensity zones: zone 1(Z1, above the ventilatory threshold (VT)), zone 2 (Z2, between VT and the respiratory compensation threshold (RCT)), and zone 3 (Z3, above the RCT). RESULTS: The values are presented as mean +/- SEM. Values of HR were significantly higher (P < 0.05) in HM1 (160 +/- 1 beats x min-1) compared with the other types of ascents. When we compared the different passes, the intensity decreased in the following order: HM1, HMS, HM2, and HM3. The average time that cyclists spent in Z3 was significantly higher in HM1 (10.7 +/- 1.4 min) with respect to the other categories. The time in Z2 was significantly higher in HMS and HM1 (43.1 +/- 1.5 and 44.3 +/- 3.1 min) than in HM2 and HM3 (21.6 +/- 1.1 and 11.9 +/- 1.1 min). The percentage of total time spent in Z3 was significantly higher in HM1 and HM3 (21.2 +/- 2.9 and 17.3 +/- 1.9%) than in HME and HM2. CONCLUSION: The ascent of mountain passes is an activity involving intense effort which is reflected in the time cyclists spend in Z3 and Z2, and is related to the category of the mountain passes involved.